The Effects of Digital eHealth Versus Onsite 2-Day Group-Based Education in 255 Patients With Irritable Bowel Syndrome: Cohort Study - Birgitte Berentsen; Camilla Thuen; Eline Margrete Randulff Hillestad; Elisabeth Kjelsvik Steinsvik; Trygve Hausken; Jan Gunnar Hatlebakk (JMIR Human Factors)
Abstract BackgroundIrritable bowel syndrome (IBS) has a high worldwide prevalence and there are few effective treatment options. Patient education can influence patient behavior that subsequently may lead to changes in attitudes and skills necessary for maintenance or improvement in management of symptom severity and quality of life. However, as postdiagnostic patient education can be resource demanding, assessment of digital approaches and verification of their effectiveness is warranted. ObjectiveThis cohort study aimed to investigate the effects of a digital web-based multidisciplinary eHealth program on the domains of symptom severity (Irritable Bowel Syndrome Symptom Severity Scale [IBS-SSS]), quality of life (irritable bowel syndrome quality of life [IBS-QOL]), anxiety and depression (Hospital Anxiety and Depression Scale), and a measure of general client satisfaction (client satisfaction questionnaire), compared with an onsite multidisciplinary 2-day group-based education program (“IBS-school”), in 2 cohorts of 255 patients with IBS. MethodsPatients diagnosed with IBS, aged 15-70 years, were enrolled after referral to the Section of Gastroenterology at Haukeland University Hospital, Norway. In total, 132 patients were recruited to the eHealth program and 123 to the IBS-school group for comparison. Data were self-reported and collected digitally at enrollment and after 3 months, between 2017 and 2019. Furthermore, 71 attending the eHealth program and 49 attending the IBS-school completed the questionnaires at 3 months. Intervention response was defined as a reduction of ≥50 points on the IBS-SSS. ResultsPatients attending the eHealth program reported a significant reduction in IBS symptom severity 3 months after treatment (n=71), compared with patients attending the IBS-school (n=50). Overall, patients categorized as intervention responders in both programs showed a significant reduction in symptom severity at 3 months. Here, 41% (29/71) of patients attending the eHealth program reported a mean IBS-SSS reduction of 103 (SD 72.0) points (PPPPP ConclusionsWe conclude that the digital multidisciplinary eHealth program has a significant effect on in a portion of patients; it is useful as a tool in disease self-management and does not result in worse symptom scores than an onsite multidisciplinary 2-day group-based education program after 3 months. We believe these results indicate that a digital eHealth approach is preferable to an onsite multidisciplinary 2-day group-based education program covering the same topics.